2c+5-84=3c+6

Simple and best practice solution for 2c+5-84=3c+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c+5-84=3c+6 equation:


Simplifying
2c + 5 + -84 = 3c + 6

Reorder the terms:
5 + -84 + 2c = 3c + 6

Combine like terms: 5 + -84 = -79
-79 + 2c = 3c + 6

Reorder the terms:
-79 + 2c = 6 + 3c

Solving
-79 + 2c = 6 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
-79 + 2c + -3c = 6 + 3c + -3c

Combine like terms: 2c + -3c = -1c
-79 + -1c = 6 + 3c + -3c

Combine like terms: 3c + -3c = 0
-79 + -1c = 6 + 0
-79 + -1c = 6

Add '79' to each side of the equation.
-79 + 79 + -1c = 6 + 79

Combine like terms: -79 + 79 = 0
0 + -1c = 6 + 79
-1c = 6 + 79

Combine like terms: 6 + 79 = 85
-1c = 85

Divide each side by '-1'.
c = -85

Simplifying
c = -85

See similar equations:

| -16x-32=-14x+55 | | 14c+5-32=3c+6 | | 9x-4-7x-10=-8x-11+17x-3 | | Y=.20x+160 | | 14c+35-4=3c+6 | | 0.0m=20.0m+a(12s) | | 25x^2+18=98 | | (5d^2-2g^5)(3g^3-h+4d^2)=0 | | 2p(p)(p)(0+2)+(p+2)=0 | | x-3(-4+9x)=16 | | 8x+3x-9x=4+2 | | 1+-8x=81+2x | | (5d^2-2g^5)-(3g^3-h+4d^2)=0 | | .50x+0.25(30)=42.5 | | [3a+8]=[4a-4] | | sqrt(8n-5)-1=2 | | 64+79= | | 2x+3x+9=6x-16 | | x-12-27x=16 | | 2d-5=d-1 | | 3+8x=4x-1 | | 3+3n=-4+2n | | 0=20+a(12) | | -16.1(t*t)+40t=4 | | (3k-1)(3k-1)=(5k+3)(3k-8) | | 1.08x=30 | | 2+-7k=20+-k | | 10x-50+15x=18x+12 | | 1m+2=6 | | (5d^2-2d^5)(3d^3-h+4d^2)=0 | | (5d^2-2d^5)-(3d^3-h+4d^2)=0 | | -3x+78=-15x-282 |

Equations solver categories